Silek As An Alternative To Maintain Character The Minangkabau Body In Learning Body Exercises Atdance Education Study Program,Padang State University - Venny Rosalina; Jamaris; Sufyarma Marsidin (CV. AFDIFAL MAJU BERKAH, 2022)
The Body Exercise course at the UNP Dance Education Study Program is a process of transforming knowledge and body dance technique skills in order to train professional body skills. The dance techniques learned in bodybuilding courses make Silek the foundation for the birth of movement. This study aims to analyze the basic movements of silek which are used as supporting materials for strengthening Minangkabau bodily techniques in the Body Exercise course at the Dance Education Study Program UNP. The results show that Silek is the basic element for Minangkabau bodybuilding and dance techniques. Body training using the silek technique trains dancing skills from the aspect of strength, accuracy and balance. Some elements of silek are also emphasized in bodybuilding training, such as: Tagak jo Step, Gelek, Balabek, Simpia, Baliak, Tagak itiak, Garak jo Garik and Raso jo Pareso. Silek is an alternative to maintain the character of the Minangkabau body in Body Exercise courses. This research is a qualitative research, using interview and observation techniques to collect data.